2007
DOI: 10.1007/bf02820846
|View full text |Cite
|
Sign up to set email alerts
|

The K-factor, Covitality, and personality

Abstract: We present a psychometric test of life history theory as applied to human individual differences using MIDUS survey data (Brim et al. 2000). Twenty scales measuring cognitive and behavioral dimensions theoretically related to life history strategy were constructed using items from the MIDUS survey. These scales were used to construct a single common factor, the K-factor, which accounted for 70% of the reliable variance. The scales used included measures of personal, familial, and social function. A second comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
147
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(165 citation statements)
references
References 40 publications
14
147
4
Order By: Relevance
“…Most interestingly, they paint strikingly different views of the slow (vs. fast) life history person depending on whether the overall or distinctive measure is used-even though overall and distinctive slow-LH scores are themselves highly correlated. If one considers only overall slow-LH scores, the results mirror the findings of previous research indicating that slow-LH people have many conventionally "positive" (meaning socially desirable) and very few conventionally "negative" (meaning socially undesirable) qualities (e.g., Figueredo et al, 2007). However, if one considers the distinctive slow-LH history scores, the results reveal how both slow-LH and fast-LH persons have adaptive strengths and weaknesses.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Most interestingly, they paint strikingly different views of the slow (vs. fast) life history person depending on whether the overall or distinctive measure is used-even though overall and distinctive slow-LH scores are themselves highly correlated. If one considers only overall slow-LH scores, the results mirror the findings of previous research indicating that slow-LH people have many conventionally "positive" (meaning socially desirable) and very few conventionally "negative" (meaning socially undesirable) qualities (e.g., Figueredo et al, 2007). However, if one considers the distinctive slow-LH history scores, the results reveal how both slow-LH and fast-LH persons have adaptive strengths and weaknesses.…”
Section: Discussionsupporting
confidence: 78%
“…Such a relationship between the average CAQ profile and the slow-LH template is not surprising as previous research has demonstrated that slow-LH (or K-factor) is associated with covitality-a composite measure of physical and psychological well-being (Figueredo et al, 2007)-and previous research has demonstrated that the average personality profile is associated with psychological adjustment (Baird et al, 2006;Borkenau & Zaltauskas, 2009;Edwards, 1957;Fleeson & Wilt, 2010;Klimstra et al, 2010;Sherman et al, 2012;Wood et al, 2007;Wood & Wortman, 2012).…”
Section: Measuring Life Historymentioning
confidence: 87%
See 1 more Smart Citation
“…The human species is characterized by a specific mating system, with a high propensity towards monogamous pairbonding, a high level of cooperation between males and females, and a high level of male investment in offspring [54], with some leeway for cultural variations [54]. Psychosocial acceleration theory posits that when the environment is harsh, individuals have an interest in diversifying their sexual and emotional investments, having multiple partners, sex without commitment and shorter committed relationships [32,51,55]. Given the costs and benefits associated with longterm relationships, it should indeed be expected that people develop different attachment styles toward their partners in harsh versus affluent environments.…”
Section: Investing In the Family: Restricted Sociosexualitymentioning
confidence: 99%
“…Empirical analyses assessing the validity of the conceptual framework of life history theory have shown considerable support for the perspective (Brumbach et al 2009;Dunkel and Decker 2010;Figueredo et al 2006Figueredo et al , 2013. In addition to construct validity analyses, the empirical literature has illustrated variance in human life history strategies related to outcomes such as health-related measures (Ellis 1988;Rushton 2000Rushton , 2004, relationship measures (Olderbak and Figueredo 2010), personality (Figueredo et al 2007;Gladden et al 2009), risktaking propensities (Ellis et al 2012;Figueredo et al 2005;Wilson and Daly 1997), and antisocial behaviors Daly and Wilson 2005;Dunkel et al , 2013Ellis 1988;Ellis et al 2012;Rowe et al 1997;Rushton 1989;Rushton and Templer 2009;Wenner et al 2013;Wilson and Daly 1997). Importantly, given the explicit focus on reproductive behaviors within life history theory, an expanding literature has illustrated considerable within-species variance in sexual behaviors among humans congruent with expectations derived from life history theory Figueredo et al 2006;Rowe et al 1997).…”
Section: Understanding Life History and Differential K Theorymentioning
confidence: 99%